Give “peace through globalization” a chance: the role of economic globalization in UAE-Israel normalization - Feldman, Nizan; Lutmar, Carmela (Frontiers in Political Science, 2025)
While the “peace through globalization” literature is primarily framed as an effort to examine whether economic globalization promotes peace, most of its models investigate whether trade reduces conflict. This study argues that by defining different stages in the transition to peace as a dependent variable, the relationship between a state’s exposure to globalization and peace is more complex than theorized in the literature. Even in our still-globalized world, where countries have numerous options for forming new economic partnerships, greater exposure to the global economy increases the appeal of establishing economic ties with certain partners. Therefore, the ability of economic interactions to foster peace is conditional to some degree on countries’ exposure to globalization. Consequently, a country’s efforts to deepen global integration can amplify the expected benefits of peace with specific nations, creating opportunities for rapprochement. By using Israel-UAE relations as a case study, we illustrate how the UAE’s strategy of diversifying its global economic ties has enhanced the benefits of cooperation with Israel, thereby supporting and strengthening normalization efforts.